2023
DOI: 10.1002/ame2.12318
|View full text |Cite
|
Sign up to set email alerts
|

A neuron‐specific Isca1 knockout rat developments multiple mitochondrial dysfunction syndromes

Abstract: Background Multiple mitochondrial dysfunction syndromes (MMDS) are rare mitochondrial diseases caused by mutation of mitochondrial iron–sulfur cluster synthesis proteins. This study established a rat model simulating MMDS5 disease in the nervous system to investigate its pathological features and neuronal death. Methods We generated neuron‐specific Isca1 knockout rat (Isca1flox/flox ‐NeuN‐Cre) using CRISPR‐Cas9 technology. The brain structure changes of CKO rats were studied with MRI, and the behavior abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The loss or depletion of Nissl bodies indicates disruption in neuronal protein synthesis and overall cellular health. This is often associated with neuronal degeneration [ 25 ], dysfunction [ 26 ], or death [ 27 ]. Consistent with previous studies, our results showed a reduction in Nissl bodies in the arsenic-exposed groups, as indicated by the lighter Nissl staining.…”
Section: Discussionmentioning
confidence: 99%
“…The loss or depletion of Nissl bodies indicates disruption in neuronal protein synthesis and overall cellular health. This is often associated with neuronal degeneration [ 25 ], dysfunction [ 26 ], or death [ 27 ]. Consistent with previous studies, our results showed a reduction in Nissl bodies in the arsenic-exposed groups, as indicated by the lighter Nissl staining.…”
Section: Discussionmentioning
confidence: 99%